Enhancing trust in takaful: a study on staff awareness at Maybank Bukit Ubi / Muhammad Hakim Azizi - Azizi, Muhammad Hakim (2025)
This study investigates methods to enhance trust in Takaful through staff at Maybank Bukit Ubi, emphasizing the critical role of trust in promoting the growth and sustainability of Takaful as a Shariah-compliant financial service. The research aims to understand how staff perceptions, awareness, and knowledge influence their trust and advocacy for Takaful products and services. A quantitative research approach, including structured surveys, was employed to gather insights from Maybank Bukit Ubi staff. The surveys were designed to capture measurable data on staff perceptions, levels of awareness, and the impact of their knowledge on trust and advocacy for Takaful. The findings highlight several key factors affecting trust, such as the level of consumer awareness, the importance of ethical and transparent practices, and the effectiveness of communication strategies. The study reveals that staff members play a vital role in shaping customer trust by serving as advocates and sources of reliable information. Additionally, the research identifies gaps in knowledge and areas where further training or resources are required to empower staff to confidently promote Takaful. Practical recommendations include enhancing educational initiatives, improving customer communication tools, and fostering a deeper understanding of Takaful principles among employees. By addressing these areas, the study seeks to build stronger trust in Takaful, not only within the institution but also among its customers.